Slovenia on the Verge of Major Changes to the Close Corporations Regulation: Evaluating the German Entrepreneurial Company (UG) and the Transferability of this Model to Slovenian Company Law - Prostor, Jerneja (65 pravne znanosti v Mariboru, 2026)
In Slovenia, intensive preparations are underway for one of the significant amendments to the Companies Act, primarily initiated by pressure from start-up companies. They are striving for a simpler establishment of a closed company. A model solution for such a trend could be found in the German entrepreneurial company (UG). The Germans introduced this as a variant of their GmbH in 2008, in response to the broad interpretation of freedom of establishment, which had led to their territory being flooded with numerous Ltd. companies. The chapter discusses other solutions in German legislation that would be sensible to introduce into the Slovenian limited liability company or a possible new legal form of company. Certain restrictions on the establishment of the company should be relaxed, and an increase in authorized capital should be permitted. It also points out key changes that will need to be adopted from Austrian solutions.